Pengawasan Terhadap Tenaga Kerja Asing Di Kabupaten Aceh Tengah - Simatupang, Namirah; Syam, Amir (Sekolah Tinggi Ilmu Hukum Muhammadiyah Takengon, 2021)
The challenges of national development related to employment have increased with the presence of free trade and industrial globalization, the presence of foreign workers is a necessity and an unavoidable challenge. The presence of foreign workers will have an impact on the absorption of local workers. The purpose of this research is to find out the supervision of foreign workers by the Office of Transmigration and Manpower in Central Aceh District. This type of research is empirical juridical, using primary data sources and secondary data. The method of data collection is done by interviews and document studies. The results of the study show that supervision of foreign workers by the Transmigration and Manpower Office in Central Aceh District is only limited to monitoring Permits to Employ Foreign Workers (IMTA) for each foreign worker employed by the company concerned. Furthermore, the authority to supervise and enforce foreign workers (TKA) is the authority of labor inspectors at the Aceh province manpower service as stipulated in Appendix letter G of Law Number 9 of 2015 concerning the Second Amendment to Law Number 23 of 2014 concerning Regional Government .